Tailoring Nutrition to Combat Treatment Failure in Type 2 Diabetes with Genetic Variants - Sarvesh Sabarathinam,; Akshay J Kumar,; Vinitha Packirisamy,; Lakshmi Thangavelu, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pharmacogenomics emphasizes the correlation between the genetic code and variations in therapeutic drug outcome or drug toxicity, or side effects. Nutrigenomics helps the identification of suitable food-based and diet-based approaches along with Equipping individuals with T2DM with knowledge about the impact of genetic polymorphisms on treatment response and the potential for personalized dietary interventions to empower them to make informed decisions about their health. An in-depth literature review was permed relevant to the treatment failure and its correlation with genetic polymorphism and its impact on genetic changes. Followed by clinical evidence of nutrient gene interaction and treatment responses were enclosed in this study. Successful implementation of nutrigenomics into clinical practice necessitates collaboration among healthcare professionals, researchers, and policymakers, enabling the integration of genetic testing, dietary assessment, and personalized nutritional interventions into routine T2DM management.Nutrigenomics, a field focusing on the interaction between genes and nutrients, holds significant potential for advancing research in individuals with T2DM who experience treatment failure due to genetic polymorphisms affecting drug transporters and targets.